How Central Should the Central Bank Be? - Blinder, Alan S (Journal of Economic Literature, 2010)
The nature and scope of the Federal Reserve's authority and the structure of its decision making are now “on the table” to an extent that has not been seen since 1935, and the Fed's vaunted independence is under some attack. This essay asks what the Federal Reserve should—and shouldn't—do, leaning heavily on the concept of economies of scope. In particular, I conclude that the central bank should monitor and regulate systemic risk because preserving financial stability is (a) closely aligned with the standard objectives of monetary policy and (b) likely to require lender of last resort powers. I also conclude that the Fed should supervise large financial institutions because that function is so closely to regulating systemic risk. However, several other functions now performed by the Fed could easily be done elsewhere. (JEL E52, E58, G21, G28)